Defects of the will in software agents contracting - Andrade, Francisco Carneiro Pacheco (2008)
The use of intelligent software agents brings along a lot of new issues in what contracting is concerned. Actually, to speak about contracts there must be two or more declarations of will, containing a consensual agreement, consisting of an offer and of an acceptance. But intelligent software agents operate in electronic commerce without any direct intervention of humans, and they have a control on their own actions and on their own inner state. So, legal difficulties obviously arise in such situations of contracting through the only intervention and interaction of autonomous intelligent systems. Thus being, the analysis of the process of formation of will and of issuing of declaration in electronic contracts negotiated (and eventually performed) by electronic software agents will be crucial to the development of intelligent inter-systemic electronic contracting. But, may the the rules of will defects be adapted to software agent contracting?